Brief Review: The Negative Impact Of Mimosin in L. leucocephala in Ruminant Animals and Processing Methods to Reduce Poisoning Effects on Ruminant Livestock - Yanuartono Yanuartono; Soedarmanto Indarjulianto; Alfarisa Nururrozi; Slamet Raharjo; Hary Purnamaningsih (Universitas Tidar, 2019)
Leucaena leucocephala, a high-quality ruminant feed, is essential for livestock production in the tropics, despite the presence of mimosine in the leaves. Mimosine, in high concentrations, can severely affect animal health and performance. Mimosine and its metabolites, 3-hydroxy-4-(1H)-piridon (DHP), are toxic to ruminants and caused hair loss, slow growth, and oral ulceration, whereas DHP is goitrogenic because it is analogous to tyrosine so resulting in goiter. Mimosine and its metabolites are the main hindrance blocks for the utilization of L.leucocephala as animal feed. Characteristic signs of L.leucocephala toxicity are alopecia, anorexia, reduced weight gain, and weight loss, excessive salivation, esophageal lesions, enlarged thyroid and low circulating concentrations of thyroid hormones. Therefore, the research workers had tried to develop different methods to eliminate the toxicological effects of mimosine and its metabolites. This paper aims to briefly review the negative effects of mimosine from L. leucocephala and its processing to reduce the toxic effects on ruminants. Keywords: Leucaena leucocephala, mimosine, toxicity, metabolites